An Adaptive Automatic Algorithm for Extracting Geological Lineaments in AL-Dibdibba Formation Basin - S. Mahdi, Alaa; A. Jawad, Laith (Iraqi Journal of Science, 2023)
Iraq is one of the Arabian area countries, which considered from the drier areason the earth, though it has two main rivers that pass through(Tigris and Euphrates);it suffers the same problem as them (drought), only the rivers' nearby regions makeuse of their water for (domestic, agricultural, and industrial purposes(.One of the usable solutions is to utilize the groundwater (especially in the desertregions). Using the Remote Sensing and geographic information system is a rapidand coast effective techniques, they provide information of large and inaccessiblearea within short span for assessing, monitoring, and management of groundwaterresources. In this study, an adaptive algorithm based on Canny edge detector noisereduction idea and directional filters scheme submitted for lineaments automaticallyextraction from LandSat7 (Enhanced Thematic Mapper Plus) ETM+ band 7 dataconsidering the lineaments spatial and spectral characteristics, yet the algorithmvalidation examined using ancillary data of the same interest (Iraq tectonic map and90m SRTM DEM). The analysis process achieved using Arc GIS 9.3 to recognizethe potential groundwater renewal and/ or accumulative zones in the selected arid tosemi-arid area (AL-Dibdibba formation basin).